PeLeP: um modelo de perfil de aprendiz orientado à aprendizagem ubíqua - Levis, Darci (Universidade do Vale do Rio do Sinos, 2007)
The ubiquitous computing brings several potentialities for the processes of teaching and learning. Of the educational point of view, the callenge it is the creation of an environment of mobile learning that provides resources adapted for the learner. In the scenario of the learning ubiquitous, the creation of a Learner Profile, that unites yours locations, interests and referring information its study he/she becomes important. This dissertation presents PeLeP – Pervasive Learning Profile, which consists in a learner profile model oriented to ubiquitous learning systems. PeLeP aims to let applications explore ubiquitous education and learning through user profiles organized by categories containing information about that learner’s daily life. Learner profiles in PeLeP are defined and enriched through inferences. These inferences are based on several factors, such as learner’s mobility between contexts, and the tasks he executes in each of them while inside a ubiquitous computing environment
PeLeP pervaise learning profile
Keywords: aprendizagem ubíqua; computação ubíqua; computação móvel; learning objects; learning styles; mobile computing; ubiquitous computer; ubiquitous learning; ubiquitous education; Ciências Exatas e da Terra